Dichlorido{N,N-dimethyl-N '- 1-(2-pyridyl)ethylidene ethane-1,2-diamine-kappa N-3,N ',N ''} manganese(II) - Hisham, N.A.I.; Ali, Hapipah Mohd; Khaledi, H.; Gwaram, N.S. (International Union of Crystallography, 2011)
The asymmetric unit of the title compound, [MnCl2(C11H17N3)], contains two crystallographically independent molecules with slightly different geometries. In each molecule, the Mn-II ion is five coordinated by the N,N',N ''-tridentate Schiff base and two Cl atoms in a distorted square-pyramidal geometry. In the crystal, C-H center dot center dot center dot Cl hydrogen bonds link adjacent molecules into a three-dimensional network.